Promoting personal safety in PSHE - Harries, Jane (Paul Chapman Pub., 2006)
Based on work done in secondary schools by the NSPCC, this PSHE curriculum resource gives young people the information and skills necessary to keep themselves 'safe'. Focusing on personal safety, the book addresses key issues such as emotional health and well-being, the ability to access help and support and family, social and sexual relationships. Each section contains a comprehensive facilitator's guide.